Konstitutive Negativität: Zur Rekonstruktion des Politischen in der negativen Dialektik Adornos - Han, Sangwon (transcript, 2016)
Astoundingly, the political potential of Adorno's negative dialectic has until now rarely been explored. Sangwon Han conceptualizes a politics of negativity in which he demonstrates that the concept of negativity in Adorno can actually present a model for politics. Adorno's negative dialectic, which creatively extends the tradition of dialectical thought on negativity from Hegel and Marx can also be understood as a theoretical framework with which politics can be established as negation and interpreted as an independent social force. However this requires the illumination of Adorno's negativity as a constitutive negativity.